2016
DOI: 10.1136/bmjdrc-2015-000160
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 30-day readmission following hypoglycemia-related emergency room and inpatient admissions

Abstract: ObjectiveHypoglycemia is a serious complication of diabetes treatment. This retrospective observational study characterized hypoglycemia-related hospital emergency room (ER) and inpatient (in-pt) admissions and identified risk factors for 30-day all-cause and hypoglycemia-related readmission.Research design and methods4476 hypoglycemia-related ER and in-pt encounters with discharge dates from 1/1/2009 to 3/31/2014 were identified in a large, multicenter electronic health record database. Outcomes were 30-day a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…Our findings are also consistent with studies of people with diabetes in North America, which have found African-American people to be at higher risk of hypoglycaemia than white European people [6,7,20,21]. Karter et al [8] performed a 7-year longitudinal study in people with Type 1 or ª 2018 Diabetes UK Type 2 diabetes prescribed insulin and/or sulfonylureas and found that African American people had consistently higher rates of severe hypoglycaemia than white Europeans, while Latino and Asian people had lower rates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are also consistent with studies of people with diabetes in North America, which have found African-American people to be at higher risk of hypoglycaemia than white European people [6,7,20,21]. Karter et al [8] performed a 7-year longitudinal study in people with Type 1 or ª 2018 Diabetes UK Type 2 diabetes prescribed insulin and/or sulfonylureas and found that African American people had consistently higher rates of severe hypoglycaemia than white Europeans, while Latino and Asian people had lower rates.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are also consistent with studies of people with diabetes in North America, which have found African‐American people to be at higher risk of hypoglycaemia than white European people . Karter et al .…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to the overall economic burden, because inpatient costs account for approximately 40% of total Medicare expenditures for dialysis. Although national epidemiology of unplanned readmissions has been described in other diseases, there are limited data on patients with ESRD on HD, especially those with non-Medicare insurance (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]8,9 Several studies focused on hospitalizations for hypoglycemia 8,10 or hyperglycemia, 8 but without placing them in the broader context of hospitalizations and readmissions. Severe dysglycemic events can be avoided with optimal transitional and ambulatory care, 11 and…”
Section: Introductionmentioning
confidence: 99%